AB0618 COMPREHENSIVE ANALYSIS OF AUTOANTIBODY PROFILE IN A TURKISH SYSTEMIC SCLEROSIS COHORT. (13th June 2020) - Temiz Karadağ, D.; Yazici, A.; Komac, A.; Erez, Y.; Birlik, M.; Akdoğan, A.; Sari, A.; Farisoğullari, B.; Kimyon, G.; Arslan, D.; Koc, E.; Koca, S. S.; et al.
Abstract : Background: Serum autoantibodies closely reflect patterns of organ involvement and disease progression in systemic sclerosis (SSc). The entire autoantibody profile is less well defined in many cohorts and the data regarding their clinical associations and frequencies is limited. Objectives: To determine the autoantibody profile of patients with SSc, as well as their clinical associations, in well-characterized inception- cohort with disease duration less than 3 years. Methods: Serum samples of 100 patients out of 105 enrolled in the study were analyzed for ANA patterns with indirect immunofluorescence (IIF) assay using HEp-20-10/primate liver mosaic IIFT kit. Sera of 96 patients were subjected to commercial line immunoassay to quantify autoantibodies against 13 different autoantigens. Results: 92 (92%) out of 100 patients were positive for ANA by IIF (Table 1 ). The speckled staining was the most pattern followed by nucleolar in 10 patients, centromere in 4, reticular in 1, nuclear in 2 and homogenous in 1. All patients (n= 96) patients were positive for at least 1 autoantibody by immunoblotting (Table 2 ). Twenty-two (49%) of patients with antiTopo I, 12 (44%) of the patients with antiCENP and 4 (22%) of the patients with antiRNAPIII were single positive. There was no difference in terms of the clinical findings when the patients with single and coexpression of these antibodies were compared. The distributions of the most frequent autoantibodies are shown in Figure 1 . Interstitial lung disease was more frequent in the patients positive for anti-Topo I (78.8%) and anti-RNAPIII (27.3%). One of the two patients with breast cancer was anti-RNAPIII positive and none of the patients have diagnosed scleroderma renal crisis. Anti-Topo I was more common in patients with dcSSc (75%) and anti-CENP in lcSSc (46.4%). Conclusion: We presented the clinical and serologic features of the Turkish SSc patients from a new inception cohort. Clinical features of the SSc patients with single or multiple antibody positivity were not different. References: None Disclosure of Interests: None declared